ADVANCES IN BATTERY TECHNOLOGY: FROM LITHIUM-ION TO BEYOND - Hamid Javaid (Bulletin of Engineering Science, Technology and Industry, 2023)
Battery technology has seen significant advancements over the past few decades, with lithium-ion batteries (LIBs) becoming the dominant energy storage solution. However, the limitations of LIBs, such as resource constraints, safety concerns, and limited energy density, have spurred research into alternative battery technologies. This paper provides a comprehensive overview of the evolution of battery technology, focusing on the advancements beyond lithium-ion batteries, including lithium-sulfur, solid-state, and metal-air batteries. We also discuss the potential of emerging technologies like sodium-ion, magnesium-ion, and organic batteries. The paper concludes with an analysis of the challenges and future prospects in the field of battery technology.